Structure-changeable luminescent Eu(III) complex as a human cancer grade probing system for brain tumor diagnosis - Wang, Mengfei; Kono, Masaya; Yamaguchi, Yusaku; Islam, Jahidul; Shoji, Sunao; Kitagawa, Yuichi; Fushimi, Koji; Watanabe, Sora; Matsuba, Go; Yamamoto, Akihisa; Tanaka, Motomu; Tsuda, Masumi; et al. (Scientific reports, 2024)
Accurate determination of human tumor malignancy is important for choosing efficient and safe therapies. Bioimaging technologies based on luminescent molecules are widely used to localize and distinguish active tumor cells. Here, we report a human cancer grade probing system (GPS) using a water-soluble and structure-changeable Eu(III) complex for the continuous detection of early human brain tumors of different malignancy grades. Time-dependent emission spectra of the Eu(III) complexes in various types of tumor cells were recorded. The radiative rate constants (kr), which depend on the geometry of the Eu(III) complex, were calculated from the emission spectra. The tendency of the kr values to vary depended on the tumor cells at different malignancy grades. Between T = 0 and T = 3 h of invasion, the kr values exhibited an increase of 4% in NHA/TS (benign grade II gliomas), 7% in NHA/TSR (malignant grade III gliomas), and 27% in NHA/TSRA (malignant grade IV gliomas). Tumor cells with high-grade malignancy exhibited a rapid upward trend in kr values. The cancer GPS employs Eu(III) emissions to provide a new diagnostic method for determining human brain tumor malignancy.